Analisis Break Even Point Sebagai Dasar Perencanaan Laba Pada Rumah Makan Ayam Bakar Aa’ Bangunrejo Lampung Tengah - Wardhana, Happy Chandra; Nusantoro, Jawoto; Sari, Gustin Padwa (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
and break even point analysis as profit planning at Aa' Bangunrejo Grilled Chicken Restaurant, Central Lampung. The theory used is the Theory of Constraint (TOC) or the Theory of Constraints. The method used in this research is descriptive qualitative. In this study, researchers used primary data through interviews. The subject of this research is Mr. Chairul as the owner of the restaurant. The data analysis method used is the calculation of cost plus pricing with the full costing method, the calculation of BEP on the basis of units and on the basis of the number of sales in rupiah. The results of this study indicate that the selling price with the application of the cost plus pricing method is higher. The details of the calculation are that there is a price difference of Rp. 5,208.3 from the CEP results of Rp. 23,741.3 and the calculation of restaurants of Rp. 18,533.3. The calculation obtained from the BEP analysis concluded that during the month of May 2022 the restaurant had experienced a profit, and the calculation in profit planning experienced an increase and decrease in profit.